A leakage correction with burnup-dependent GPS method in two-step core depletion analysis. (April 2023) - Jeong, Hae Sun; Oh, Taesuk; Kim, Yonghee
Highlights: Removed the term of "per unit volume" in Eq.(1) . Modified some expressions in Eq.(7) and specified the meaning of the abbreviations. Abstract: The aim of this study is to introduce a burnup-dependent GPS † method in the pin-resolved two-step reactor depletion analysis and to verify how effectively leakage correction works in terms of reactor eigenvalue ( k eff ) and power distribution. The burnup-dependent GPS function sets were generated based on the different color-set models with various conditions, considering the adjacent non-target fuels with fresh or burned fuels at each burnup step. In the functionalization stage, the cross-section-dependent SPH factors were parameterized considering the current-to-flux ratio (CFR) indicating the integrated leakage information and the spectral index (SI) representing the fluctuations in the neutron spectrum. The computational performance for the burnup-dependent GPS method was evaluated with a modified PWR benchmark problem for a UOX-loaded small reactor. The lattice calculations for the group constants generation and the reference core calculations were performed using the DeCART2D transport code. The nodal depletion calculations were performed with an in-house nodal expansion method (NEM) code implemented with a hybrid coarse mesh finite difference (HCMFD) solver. The two-step macroscopic depletion calculations were performed based on 4 types of conditions named; (1) w/o GPS, (2) w/BOC-GPS, (3) w/BU-GPS(F), and (4) w/BU-GPS(F&B), where letters 'F' and 'B' within the parenthesis indicate 'Fresh' and 'Burned' respectively. As a result, by individually applying two different GPS functions in the boundaries and internal area of the assembly (i.e., w/BU-GPS(F&B)), it shows a good performance with low errors at a sufficiently acceptable level in terms of reactivity and the pin-wise power distribution. † GPS: Generalized equivalence theory (GET) Plus Super-homogenization (SPH).